Rheumatoid Arthritis Impacts on the Independent Relationships between Circulating Adiponectin Concentrations and Cardiovascular Metabolic Risk - Patrick H. Dessein; Gavin R. Norton; Margaret Badenhorst; Angela J. Woodiwiss; Ahmed Solomon (Mediators of Inflammation)
Adiponectin and leptin are likely involved in the pathophysiology of rheumatoid arthritis (RA) and therefore potential new therapeutic targets. Adiponectin inhibition could be expected to enhance cardiovascular metabolic risk. However, it is unknown whether RA changes the influence of adipokines on cardiovascular metabolic risk. We determined whether RA impacts on the independent relationships of circulating leptin and adiponectin concentrations with cardiovascular risk factors and carotid intima-media thickness (cIMT) in 277 black African subjects from a developing population; 119 had RA. RA impacted on the relationships of adiponectin concentrations with lipid concentrations and blood pressure, independent of confounders including adiposity (interaction P<0.05). This translated into an association of adiponectin concentrations with more favorable lipid variables including HDL cholesterol (P=0.0005), non-HDL cholesterol (P=0.007), and triglyceride (P=0.005) concentrations, total cholesterol-HDL cholesterol (P=0.0002) and triglycerides-HDL cholesterol (P=0.0003) ratios, and higher systolic (P=0.0006), diastolic (P=0.0004), and mean blood pressure (P=0.0007) in RA but not non-RA subjects. Leptin was not associated with metabolic risk after adjustment for adiposity. The cIMT did not differ by RA status, and adipokine concentrations were unrelated to atherosclerosis. This study suggests that leptin and adiponectin inhibition may not alter overall cardiovascular risk and disease in RA.